PENERAPAN METODE VAK (VISUAL, AUDITORI, KINESTETHIC) PADA PEMBELAJARAN MENULIS TEKS PUISI - Rosita Wulandari; Mia Sumiarsih; Rochmat Tri Sudrajat (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Language skills have four skills, namely listening, reading, writing and speaking. The students 'diverse abilities in material capture during the learning process, make educators have to be able to set methods that are suitable for students' abilities. In addition to the selection of methods, the lack of desire of students during poetry learning is due to a lack of vocabulary that makes it difficult for students to put their ideas into writing. By creating poetry texts students can actually help increase vocabulary and sensitivity. For this reason, through routine education and writing practice, it can help students increase their vocabulary. Writing poetry can be done according to students' varied abilities. With the VAK method (visual, auditory, kinesthetic) students can appreciate their poetry with the same understanding through their respective abilities. This study uses the pre-experimental design method. The pre-experimental design research design applied is a one-group pretest-posttest design. This design consists of one class to measure students' abilities before and after being given treatment. From the results of data analysis on the ability to write poetry texts from the scores of students' knowledge and skills in writing poetry, it was concluded that students of class X IT Development Vocational School were able to make poetry texts better by learning using the VAK method can be seen from the average results before using the VAK method (65.04) and the average after using the VAK method (77.36) which has been tested for normality, homogeneity, and significant differences